Women’s education notes during the franco regime: ‘profession: her sex’ (1936-1975) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2022)
This paper aims to examine the way in which the Spanish school textbooks used during the Franco dictatorship, strongly impregnated with Catholic doctrine, contributed to the construction of a feminine identity centred around marriage and motherhood. It is historical-educational research that analyses two primary sources: the Encyclical Humanae Vitae by Pope Paul VI and the Álvarez Encyclopedia: Professional Initiation. The results reveal the existence of a hidden political-social curriculum whose main purpose was to legitimise a system of domination over the female gender.
Keywords: Sex Education; Francoism; Indoctrination; National Catholicism